Skeletal Muscle Purine Nucleotide Degradation and Atrophy: Cause or Consequence of Increased Uric Acid Production - Miller, Spencer G (East Carolina University, 2022)
Elevated serum uric acid is a risk factor for mortality in diseases and critical illnesses associated with skeletal muscle atrophy. Uric acid is generated by xanthine oxidoreductase (XOR) and XOR inhibitors can partially attenuate muscle atrophy. Whether purine nucleotide degradation in atrophying muscle fibers contributes to increased XOR activity and serum uric acid, and whether uric acid is sufficient to induce muscle atrophy are unknown. Aim 1. To determine if purine nucleotide degradation is increased in atrophying skeletal muscle and its contribution to elevated uric acid production. Muscle atrophy was induced in mice by fasting and dexamethasone (DEX), and C2C12 myotubes by DEX and constitutively active FoXO3 (caFoXO3). Purines (hypoxanthine, xanthine, uric acid) were measured in serum, extensor digitorum longus (EDL) incubation buffer, or culture media by ultra-performance liquid chromatography (UPLC). Fasting and DEX significantly increased serum uric acid and uric acid release from atrophying EDL muscles. In myotubes DEX- and caFoXO3-induced atrophy caused increased hypoxanthine and xanthine (uric acid precursors) efflux, but little to no uric acid due to lack of XOR expression. Co-culturing atrophying myotubes with endothelial cells (which did express XOR), increased media uric acid solely from the oxidation of myotube purines. These findings demonstrate that purine nucleotide degradation coincides with increased protein degradation in atrophying skeletal muscles. Increased purine release from muscle cells can drive XOR activation in XOR-expressing cells and contributes to increased serum uric acid. Aim 2. To determine if uric acid can directly increase muscle protein degradation and cause muscle atrophy. C2C12 myotubes were treated with physiological levels (175, 350, or 700 µM) of uric acid for 48 hours. Myotube proteins were labeled with 13C15N-Phe and changes in 13C15N-Phe were quantified by UPLC and used to calculate protein degradation rates. Media and intracellular uric acid were determined by UPLC. Uric acid exposure did not increase protein degradation rates or reduce total protein in culture wells. Media uric acid was not reduced after 48 h but intracellular uric acid was significantly increased in myotubes. These findings demonstrated that while uric acid can accumulate in muscle cells, it does not directly increase muscle protein degradation or cause atrophy.
Keywords: AMP deaminase; Uric acid; Muscular atrophy; Xanthine oxidase; Muscle proteins